2024
DOI: 10.3390/antiox13020184
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glutathione and Its Precursors in Type 2 Diabetes

Dawn Tuell,
George Ford,
Evan Los
et al.

Abstract: Type 2 diabetes (T2D) is a major worldwide health crisis affecting about 6.2% of the world’s population. Alarmingly, about one in five children in the USA have prediabetes. Glutathione (GSH) and its precursors play a promising role in the prevention and management of type T2D. Oxidative stress (OxS) is a probable factor in both T2D initiation and progression. GSH is the major cytosolic water-soluble chemical antioxidant and emerging evidence supports its role in improving T2D outcomes. Dietary supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 118 publications
(179 reference statements)
0
4
0
Order By: Relevance
“…The redox state of the GSH/GSSG couple serves as a leading indicator of a redox environment. Both GSH and GSSG are exported from cells through multidrug resistance protein; extracellular GSH is metabolized by membrane-bound γ-glutamyl transpeptidase into cysteinylglycine and γ-glutamyl products, and dipeptidase hydrolyzes cysteinylglycine to cysteine and glycine [31]. We observed markedly diminished GSH levels in the LM and HM groups in the second set of patients.…”
Section: Direct Oxidative-stress-related Metabolitesmentioning
confidence: 66%
“…The redox state of the GSH/GSSG couple serves as a leading indicator of a redox environment. Both GSH and GSSG are exported from cells through multidrug resistance protein; extracellular GSH is metabolized by membrane-bound γ-glutamyl transpeptidase into cysteinylglycine and γ-glutamyl products, and dipeptidase hydrolyzes cysteinylglycine to cysteine and glycine [31]. We observed markedly diminished GSH levels in the LM and HM groups in the second set of patients.…”
Section: Direct Oxidative-stress-related Metabolitesmentioning
confidence: 66%
“…The same can be said for ANPEP, whose expression level is increased both in the plasma and beta cells of the pancreatic islets in patients with type 2 diabetes [23,50,96]. The main assumption is that increased expression of amino acid and peptide metabolism enzymes is required to provide amino acid precursors for the biosynthesis of glutathione, the deficit of which is considered a primary cause of type 2 diabetes [21,31,35]. Numerous studies (reviewed in [22]) have shown that glutathione deficiency and impaired redox homeostasis are etiologically associated with key changes found in type 2 diabetes, such as oxidative stress, mitochondrial dysfunction, endoplasmic reticulum stress, disruption of the ubiquitin-proteasome system and autophagy, disruption of insulin secretion, beta cell dysfunction, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Third, decreased glutathione levels are closely correlated with the pathological conditions found in T2D, and replenishment of glutathione deficiency improves them. These pathological changes include oxidative stress and mitochondrial dysfunction [31,32,3537], β-cell dedifferentiation and failure [38], impaired glucose tolerance, insulin secretion [3941] and sensitivity [42,43]. In addition, the depletion of endogenous glutathione is correlated with increased blood glucose levels and contributes to the complications of type 2 diabetes [33,34,38].…”
Section: Introductionmentioning
confidence: 99%
“…GSH plays a crucial role in maintaining cellular redox homeostasis and regulating various cell functions such as cell cycle, apoptosis, immunological defense, and pathological abnormality [19,20,52,53]. GSH also interacts with other enzymes and proteins, including glutathione peroxidases and glyoxylases, to engage and regulate cellular processes [20,52].…”
Section: Discussionmentioning
confidence: 99%